Cardiac structure and function 1.5 years after COVID-19: results from the EPILOC study - Schellenberg, Jana; Matits, Lynn; Bizjak, Daniel Alexander; Deibert, Peter; Friedmann-Bette, Birgit; Göpel, Siri; Merle, Uta; Niess, Andreas; Frey, Norbert; Morath, Oliver; Erz, Gunnar; Peter, Raphael Simon; et al. (Infection, 2025)
Impaired left and right ventricular (LV/RV) function during acute SARS-CoV-2 infection has been predominantly reported in hospitalized patients, but long-term cardiac sequelae in large, well-characterized cohorts remain inconclusive. This study evaluated cardiac structure and function in individuals with post-Coronavirus disease (COVID) syndrome (PCS) compared to recovered controls (CON), focusing on associations with cardiopulmonary symptoms and rapid physical exhaustion (RPE).